Language and music as cognitive systems - Rebuschat, Patrick (Oxford : Oxford University Press, 2012)
The past 15 years have witnessed an increasing interest in the comparative study of language and music as cognitive systems. This book presents an interdisciplinary study of language and music, exploring the following core areas - structural comparisons, evolution, learning and processing, and neuroscience.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psycholinguistics; Music and language; Cognitive science